A child's introduction to the environment : the air, earth, and sea around us--plus experiments, projects, and activities you can do to help our planet! - Driscoll, Michael, 1973-; Driscoll, Dennis M.; Hamilton, Meredith (New York : Black Dog & Leventhal Publishers, 2008)
Discusses a variety of environmental sciences topics, including global warming, food chains, and desertification, along with a collection of experiments and conservation activities.
Our wonderful world -- Talking on water -- The land we live on -- The air around us -- We've got the whole world --
Includes bibliographical references (page 95) and index.
"Includes a reusable lunch sack, stickers with save-the-Earth messages, and a poster from NRDC's Green Squad!"--Cover.
Keywords: Environmental sciences -- Experiments -- Juvenile literature; Environmentalism -- Juvenile literature; Environmental protection